Sharing vulnerability: A duoethnographic enquiry into the development of digital competencies at a South African university - Andrianatos, Kristien; Morelli, Janelize (Critical Studies in Teaching and Learning, 2024)
The duoethnographic enquiry discussed in this article grapples, in a dialogical way, with our experiences of professional learning while seeking to increase our digital competencies. The process involved happened while we were learning to use Mentimeter, an interactive presentation software. The purpose of this duoethnographic enquiery is not to provide solutions or shortcuts through a sharing of our professional learning journey. Rather we share our experiences in the hope that other higher education (HE) educators will join the conversation and reflect on their digital competencies journey. In this paper, we first present the background followed by a brief discussion of the HeDiCom framework of HE educators’ digital competencies. Then we briefly discuss duoethnography as a method. Our three main findings are presented as conversations, followed by a discussion in which we weave the insights from our conversations into a critical reflection on the applicability of the HeDiCom framework.